Evolution of Fixed partial design - A review - J Brintha Jei; B Muthukumar (Wolters Kluwer Medknow Publications, 2012)
Records of the replacement of lost teeth by artificial means reach back into ancient times. Earliest efforts probably applied only to a few teeth, served principally to repair damaged appearance and to restore the facility of normal speech. As time went on, the scope and function of dental prosthetic appliances were gradually increased. Impelled, most likely by the same ambitions which prompt modern invention and research, dental prosthesis, together with all other branches of dentistry, slowly grew to its present stage of development.